Effects of low-Z and high-Z impurities on divertor detachment and plasma confinement. (August 2017) - Wang, H.Q.; Guo, H.Y.; Petrie, T.W.; Leonard, A.W.; Thomas, D.M.; Watkins, J.G.; ,
Highlights: From DIII-D experiments, with N2, Ne and Ar seedings, the upstream plasma density for detachment onset decreases with increasing the impurity content. The confinement and pedestal pressure are correlated with the impurity and the ratio of separatrix loss power to the H-mode threshold power. N2 seeding shows different behaviors at different flow rates but exhibits good confinement comparable with non seeding plasmas. Neon is worse. And Argon has lowest confinement due to radiation effects. Abstract: The impurity-seeded detached divertor is essential for heat exhaust in ITER and other reactor-relevant devices. Dedicated experiments with injection of N2, Ne and Ar have been performed in DIII-D to assess the impact of the different impurities on divertor detachment and confinement. Seeding with N2, Ne and Ar all promote divertor detachment, greatly reducing heat flux near the strike point. The upstream plasma density at the onset of detachment decreases with increasing impurity-puffing flow rates. For all injected impurity species, the confinement and pedestal pressure are correlated with the impurity content and the ratio of separatrix loss power to thel -H transition threshold power. As the divertor plasma approaches detachment, the high-Z impurity seeding tends to degrade the core confinement owing to the increased core radiation. In particular, Ar injection with up to 50% of the injected power radiating in the core cools the pedestal and core plasmas, thus significantly degrading the confinement. As for Ne seeding, medium confinement with H98 ∼0.8 can be maintained during the detachment phase with the pedestal temperature being reduced by about 50%. In contrast, in the N2 seeded plasmas, radiation is predominately confined in the boundary plasma, which leads to less effect on the confinement and pedestal. In the case of strong N2 gas puffing, the confinement recovers during the detachment, from ∼20% reduction at the onset of the detachment to greater than unity comparable to that before the seeding. The core and pedestal temperatures feature a reduction of 30% from the initial attached phase and remain nearly constant during the detachment phase. The improvement in confinement appears to arise from the increase in pedestal and core density despite the temperature reduction.